'We know it works but does it last?' The implementation of the KEEP foster and kinship carer training programme in England. (October 2016) - Roberts, Rosemarie; Glynn, Georgia; Waterman, Colin
Recent years have seen an increased availability of well-researched parenting programmes but few are designed to address the specific needs of foster carers, including kinship carers, or are able to demonstrate longer-term outcomes. The KEEP training programme (Keeping foster and kinship carers trained and supported) was developed by Dr Patricia Chamberlain in the US state of Oregon and brought over to England in 2009 by the Department for Education (DfE) as part of the drive to improve outcomes for looked after children. KEEP is designed to strengthen foster and kinship carer parenting skills, reduce foster children's behavioural and emotional difficulties and increase placement stability. Training programmes for carers of children aged from three to 17 are now running in 24 local authorities across the country. The implementation of the KEEP programme in England, supported by the National Implementation Service, includes outcome data on 572 children and young people and their carers that demonstrate significant improvements in child problem behaviour and carer stress, and positive changes in parenting discipline style consistent with findings from the original large randomised controlled trial. In addition, longer-term outcome data for six- and 12-month post-group follow-up for KEEP Standard (for carers of children aged 5–12 years) and KEEP Safe (for carers of adolescents) show that significant improvements in behavioural difficulties, foster carer stress and parenting discipline style are all maintained. Evidence for longer-term improvements in placement stability is currently limited by a lack of comparative data.